2021
DOI: 10.3389/feart.2021.730162
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of ULF Magnetic Waves Before the Taiwan Chi-Chi 1999 Earthquake

Abstract: The ultra low frequency (ULF) electromagnetic (EM) wave activity usually recorded on Earth’s ground has been found to depend on various types of space weather. In addition ULF waves observed before an earthquake have been hypothesized to be a result of geotectonic processes. In this study we elaborate for the first time the origin of sub-ULF (<1 msec) magnetic field waves before an earthquake (Chi-Chi/Taiwan, 20.9.1999) by comparing simultaneously obtained measurements in the interplanetary space (ACE s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 144 publications
(202 reference statements)
0
1
1
Order By: Relevance
“…This means that the earthquake process must be preceded by the crack generation within the lithosphere that also could generate electromagnetic signals. This contradicts those claims that consider the space weather and solar activity as the main source of pre-failure electromagnetic signals [ 84 ]. Despite this, there is one manner in which space weather could influence the lithospherical cracking.…”
Section: Resultscontrasting
confidence: 57%
“…This means that the earthquake process must be preceded by the crack generation within the lithosphere that also could generate electromagnetic signals. This contradicts those claims that consider the space weather and solar activity as the main source of pre-failure electromagnetic signals [ 84 ]. Despite this, there is one manner in which space weather could influence the lithospherical cracking.…”
Section: Resultscontrasting
confidence: 57%
“…In this study, we will first compile the precursor times, T, of TIR/OLR anomalies before the 27 earthquakes and then explore the possible correlation between the precursor time and the mainshock magnitude. As suggested by several authors (e.g., Campbell, 2009;Thomas et al, 2009a,b;Masci, 2010Masci, , 2011aMasci, ,b,c, 2012Masci and Di Persio, 2012;Anagnostopoulos, 2021), it is necessary to further study the reliability and intrinsic significance of observed anomalies based on physical and chemical mechanisms. In the followings, the earthquake magnitude is the local magnitude, M L , determined by the Central Weather Bureau (CWB) (Shin, 1992).…”
Section: Introductionmentioning
confidence: 98%